Efficient Image Transmission over WVSNs Using Two-Measurement Matrix Based CS with Enhanced OMP - Hemalatha Rajendran; Radha Sankararajan; Jalbin Justus (International Journal of Distributed Sensor Networks)
WVSN is a collective network of motes containing visual sensors. The nodes in the network are capable of acquiring, compressing, and transmitting successive images to the sink. To increase the lifetime of such network, it is essential to reduce the amount of dataflow across the network without losing the integrity. This paper proposes a CS-based image transmission system to reduce the number of measurements required to represent the image. It utilizes a two-measurement matrix-based CS. TMM with CS leads to 2.8% to 6.7% and 0.67% to 7.9% reduction in the number of measurements compared to one MM-based CS while using DCT and binary DCT, respectively. Similarly, TMM with NUS CS leads to 5% to 40% (DCT) and 1.4% to 20% (binDCT) reduction in the number of measurements than one-measurement matrix-based NUS CS. An Enhanced Orthogonal Matching Pursuit algorithm is also proposed, which produces nearly 2% to 26% better recovery rate with the same number of measurements than the conventional OMP algorithm. Reduced measurements and better recovery rate achieved will enhance the lifetime of the WVSN, with considerable image quality. Rate distortion analysis of the proposed methodology is also done.